2016
DOI: 10.3390/ijms17091356
|View full text |Cite
|
Sign up to set email alerts
|

Family Growth and Survival Response to Two Simulated Water Temperature Environments in the Sea Urchin Strongylocentrotus intermedius

Abstract: Heat tolerance is a target trait in the selective breeding of the sea urchin Strongylocentrotus intermedius, as it plays an important role in the survival and growth of cultured S. intermedius during summer. We investigated family growth and survival response to two temperature treatments to evaluate the genotype by temperature interaction (GEI) in the family selection of S. intermedius. Sea urchins from 11 families were exposed to two simulated water temperature environments—high temperature (HE) and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…For test diameter growth rate, however, a significant family by density interaction effect was found, meaning that families' test diameter growth responded differently to stocking density variation. In S. intermedius , our studies (Chang et al, ; Zhang et al, ) reported the significant family by environment interaction effects on survival, growth and feed conversion rate. A preliminary hypothesis is that, when the environment variation is large in scale, significant family by environment interaction effects on growth rate are easily found, whereas when the environment involves the extreme factor level, a significant family by environment interaction effect on survival is easily found.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…For test diameter growth rate, however, a significant family by density interaction effect was found, meaning that families' test diameter growth responded differently to stocking density variation. In S. intermedius , our studies (Chang et al, ; Zhang et al, ) reported the significant family by environment interaction effects on survival, growth and feed conversion rate. A preliminary hypothesis is that, when the environment variation is large in scale, significant family by environment interaction effects on growth rate are easily found, whereas when the environment involves the extreme factor level, a significant family by environment interaction effect on survival is easily found.…”
Section: Discussionmentioning
confidence: 63%
“…Its offspring should be cultured in a relatively lower stocking density. Family reranking effect has been proven to be the main reason causing significant family by environment, diet, and temperature interactions by our studies on S. intermedius (Chang et al, ; Wang et al, ; Zhang et al, ) and other studies in other aquatic animals (Pierce et al, ).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations